Vitamin D Deficiency in the Gulf Cooperation Council: Exploring the Triad of Genetic Predisposition, the Gut Microbiome and the Immune System - Singh, Parul; Kumar, Manoj; Al Khodor, Souhaila (Frontiers in Immunology, 2019)
Vitamin D (VD) is a fat soluble secosteroid that is primarily synthesized in the skin upon exposure to Ultraviolet B (UVB) sun rays. VD is essential for the growth and development of bones and helps in reducing inflammation by strengthening muscle and the immune system. Despite the endless supply of sunlight in the Gulf Cooperation Council (GCC) countries, VD deficiency in the general population at various age groups remains alarmingly high. In parallel runs the increasing prevalence of acute and chronic illnesses including, autoimmune diseases, cancer, type 2 diabetes mellitus, cardiovascular disease and Inflammatory bowel disease in the adult as well as pediatric population of these countries. The exact association between VD deficiency and chronic disease conditions remains unclear, however, studies have focused on the mechanism of VD regulation by assessing the role of the VD associated proteins such as VDR (Vitamin D receptor) and VDBP (Vitamin D Binding protein) as these proteins are integral parts of the VD signaling pathway. VDR is known to regulate the expression of more than 200 genes across a wide array of tissues in the human body, indicating that a genetic predisposition may play a role in controlling the VD levels. Moreover, reduced VD level and downregulation of VDR have been linked to gut dysbiosis, highlighting an intriguing role for the gut microbiome in the vitamin D metabolism. However, this role is not fully described yet. In this review, we aim to expand our understanding of the causes of VD deficiency in the GCC countries and explore the potential relationship between the genetic predisposition, VD levels, and gut microbiome composition. Trying to unravel this complex interaction may aid in understanding the mechanism by which VD contributes to various disease conditions and will pave the way towards new therapeutics used to treat VD deficiency and its associated outcomes.